2021
DOI: 10.1038/s41598-021-99505-4
|View full text |Cite
|
Sign up to set email alerts
|

High alert drugs screening using gradient boosting classifier

Abstract: Prescription errors in high alert drugs (HAD), a group of drugs that have a high risk of complications and potential negative consequences, are a major and serious problem in medicine. Standardized hospital interventions, protocols, or guidelines were implemented to reduce the errors but were not found to be highly effective. Machine learning driven clinical decision support systems (CDSS) show a potential solution to address this problem. We developed a HAD screening protocol with a machine learning model usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…Finally, one article26 described an algorithm capable of screening high alert drug errors from prescriptions.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Finally, one article26 described an algorithm capable of screening high alert drug errors from prescriptions.…”
Section: Resultsmentioning
confidence: 99%
“…Eight publications14 15 17–19 23 24 26 used supervised ML models (online supplemental table 1); unsupervised ML algorithms (online supplemental tale 2) were used in three publications 16 20 25…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Z Xiong, D Wang, X Liu, et al (12) used a new graph neural network structure (Attentive FP), which uses a graph attention mechanism to achieve learning from relevant drugs in a data set, and experimental results showed that At tent ive FP achieve d st ate -of-the-art prediction performance in various datasets. P Wongyikul, N Thongyot, P Tantrakoolcharoen, et al (13) developed an had screening protocol using Gradient Boosting Classifier machine learning model and screening parameters to identify HAD prescription error events from drug prescriptions. The experimental results show that machine learning plays an important role in screening and reducing HAD prescription errors and has potential benefits.…”
Section: Related Workmentioning
confidence: 99%